BS EN 4884. Aerospace series. Steel X3CrNiMoAl (13-8-2). Vacuum induction melted and consumable electrode remelted. Solution treated and precipitation treated. Bars for machining. a or D ≤ 200 mm. 1 200 MPa ≤ Rm ≤ 1 350 MPa. (20th May 2021) - British Standards Institution
No abstract available